Exogenous Sodium Chloride Explores the Mechanisms For Hyperosmotic Stress Acclimation in Liverwort Marchantia Polymorpha - Tompa, NH; Uddin, M Mohi; Biswas, MS; Ghosh, TK (Annals of Bangladesh Agriculture, 2023)
In contrast to angiosperms, the mechanisms of hyperosmotic stress responses in liverworts, the evolutionarily important land plants remain more or less elusive. The present investigation was set with liverwort, Marchantia polymorpha to find out the approaches essential for hyperosmotic stress acclimation in distant land plants. The gemmae of M. polymorpha cultured in ½ B5 medium were subjected to control (0 mM NaCl) and osmotic stressed conditions led by 50 mM and 100 mM NaCl to find their morphological, biological and physiological responses. Compared to non-stress control, the thallus body of M. polymorpha showed strong growth inhibition while acclimating to hyperosmotic stress led by 100 mM NaCl. The significant reduction of chlorophyll content and tissue damage were recorded by hyperosmotic stress led by 100 mM NaCl compared to control. The negligible tissue damage and more or less similar chlorophyll content were recorded in control and by 50 mM NaCl. Further, the gemmalings showed enhanced accumulation of osmolytes proline and soluble sugar by 100 mM NaCl compared to the control which was consistent with the increased accumulation of soluble sugar by hyperosmotic stress led by 0.2 M sucrose. Hyperosmotic stress led by 100 mM NaCl showed a higher rate of electrolyte leakage in the gemmalings which was consistent with the higher amount of lipid peroxidation; malondialdehyde and hydrogen peroxide in the gemmalings treated with 100 mM NaCl compared to the control. However, the activity of enzymatic antioxidants such as superoxide dismutase; catalase; ascorbate peroxidase; dehydroascorbate reductase and glutathione S-transferase were greatly induced by 100 mM NaCl as compared to control. Therefore, the findings suggest that the basal land plants liverworts followed morpho-physiological alterations during acclimation to hyperosmotic stress which were crucial for the terrestrialization of land plants. Ann. Bangladesh Agric. (2022) 26 (2) : 1-18